29 Human induced pluripotent stem cell-derived cardiomyocytes serve as in vitro model of cardiac hypertrophy. Issue 20 (23rd September 2011) - Foldes, G; Mioulane, M; Chahine, M N; Schneider, M D; Harding, S E
Abstract : The authors have requested their abstract is retracted.